2014
DOI: 10.1016/j.celrep.2014.05.035
|View full text |Cite
|
Sign up to set email alerts
|

V-ATPase/mTOR Signaling Regulates Megalin-Mediated Apical Endocytosis

Abstract: mTOR kinase is a master growth regulator that can be stimulated by multiple signals, including amino acids and the lysosomal small GTPase Rheb. Recent studies have proposed an important role for the V-ATPase in the sensing of amino acids in the lysosomal lumen. Using the Drosophila wing as a model epithelium, we show here that the V-ATPase is required for Rheb-dependent epithelial growth. We further uncover a positive feedback loop for the control of apical protein uptake that depends on V-ATPase/mTOR signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…Lysosomal mTOR-v-ATPase signaling was shown to control the expression of megalin and thereby regulating apical protein uptake in Drosophila epithelial cells and proximal tubular cells in mice. 20 Moreover, detailed analysis of the progression toward a Fanconi syndrome in Ctns 2/2 mice revealed a gradual loss of megalin and cubulin in kidney proximal tubules, resulting in extending the defect of endocytosis and tubular proteinuria. 21 Together with these observations, our data indicate that defective mTORC1 signaling upon absence of functional cystinosin could result in impaired megalin expression in proximal tubular cells, leading to proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal mTOR-v-ATPase signaling was shown to control the expression of megalin and thereby regulating apical protein uptake in Drosophila epithelial cells and proximal tubular cells in mice. 20 Moreover, detailed analysis of the progression toward a Fanconi syndrome in Ctns 2/2 mice revealed a gradual loss of megalin and cubulin in kidney proximal tubules, resulting in extending the defect of endocytosis and tubular proteinuria. 21 Together with these observations, our data indicate that defective mTORC1 signaling upon absence of functional cystinosin could result in impaired megalin expression in proximal tubular cells, leading to proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…9 This is in contrast to recently published data, in which long-term (6 months) rapamycin treatment was shown to lead to a reduced MEGALIN expression in mice. 24 However, it has been recognized that long-term administration of rapamycin in high doses additionally inhibits mTORC2 and exerts cytotoxic effects. 25 In agreement, long-term follow-up studies (3 months) in our double-knockout RapRic DTubule mice showed a reduced MEGALIN expression, whereas Rap DTubule mice maintained a stable MEGALIN expression.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the Tor pathway acting through V-ATPase to expand the apical domain. Published data indicate that Tor regulates the expression of specific VATPase subunits (Gleixner et al, 2014) and, accordingly, we find that overexpression of Rheb, or of an activated form of the Tor downstream effector S6 kinase (S6k SDTETE ) (Barcelo and Stewart, 2002), does not suppress the cnj mutant terminal cell defects. These data imply that Tor acts genetically upstream of the V-ATPase (supplementary material Fig.…”
Section: Mutations In the Tor Pathway Phenocopy Okg And Cnjmentioning
confidence: 71%
“…In some epithelia, vATPase itself is apical (Hurtado-Lorenzo et al, 2006;Liegeois, 2006), and Kanda et al (2013) established a direct interaction between Atp6ap2, an accessory subunit of the vATPase, and the Par3 polarity protein in mice; furthermore, tissue-specific Atp6ap2 knockout mice displayed severe retinal polarity defects. Recent work from the Simons laboratory (Gleixner et al, 2014) suggests that vATPase function, together with mTOR signaling, is essential for apical endocytosis and apical surface area growth. Our results in a distinct epithelium are consistent with a role of vATPase in the regulation of apical surface area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation